A case of gangrenous cystitis with bilateral hydronephrosis 10 years after radiotherapy - Mariko Oniwa; Yuki Kataoka; Midori Yamada; Takuya Miyagawa; Takuro Sunada; Hideyuki Konishi; Gen Suzuki; Yoko Fujita (Journal of General and Family Medicine)
Abstract An 84‐year‐old woman who was admitted for protein‐losing gastroenteropathy associated with radiation enteritis 10 years after pelvic radiotherapy developed pyelonephritis. She became anuric despite having an indwelling bladder catheter. Imaging studies revealed bladder wall thickening, bilateral hydroureter formation, and hydronephrosis. Autopsy findings led to a diagnosis of gangrenous cystitis (GC). Our case indicates that radiation‐induced late effects may be an indirect cause of GC, not a direct cause as previously suggested, and that GC may induce bilateral vesicoureteral junction obstruction.